Molecular epidemiological analysis of Mycobacterium tuberculosis isolates from rural population of nationwide tuberculosis prevalence survey in Mongolia (Central Asian Journal of Medical Sciences, 2025)
Objective: Mongolia is among the 30 high-burden countries for TB and DR-TB. Whole-genome sequencing (WGS) offers precise insights into TB transmission, strain diversity, and antimicrobial resistance (AMR), which are vital for TB control strategies. This study aimed to investigate the molecular epidemiology, lineage distribution, transmission clustering, and drug resistance patterns of M.tuberculosis collected from rural areas of Mongolia using NGS.Methods: A total of 50,194 individuals were screened in a national TB prevalence survey conducted according to WHO guidelines. From rural participants, 102 TB isolates were obtained; 100 with sufficient DNA quality were subjected to WGS. Bioinformatics analyses included lineage identification, AMR mutation profiling, and phylogenetic and clustering analyses. Results: Among the 100 isolates, lineage 2 (Beijing genotype) accounted for 72.0% and lineage 4 (Euro-American) for 28.0%. The Beijing type was dominant across all regions, especially the central region (84.6%) and showed high clustering (56.4%). A total of 13 clusters (≤12 SNVs) were identified; 86.6% were Beijing strains. MDR-TB comprised 10% of isolates, with 100% of MDR-TB strains belonging to the Beijing genotype. Resistance to isoniazid (23%) was common. Mutations associated with resistance were mainly found in katG, inhA, rpoB, pncA, rpsL, rrs, and embB genes. No resistance was observed to new drugs such as bedaquiline, linezolid, or clofazimine. Conclusions: In rural of Mongolia, M. tuberculosis Lineage 2 (modern Beijing genotype) is predominant, accounting for 72% of cases, with consistent distribution across geographic locations. Beijing strains demonstrated higher drug resistance compared to Euro-American types. Importantly, no resistance was detected to newly introduced TB drugs.